Critical Care Database Comprising Patients With Infection - Xu, Ping; Chen, Lin; Zhu, Yuanfang; Yu, Shuai; Chen, Rangui; Huang, Wenbin; Wu, Fuli; Zhang, Zhongheng (Frontiers in Public Health, 2022)
Patients treated in the intensive care unit (ICU) are closely monitored and receive intensive treatment. Such aggressive monitoring and treatment will generate high-granularity data from both electronic healthcare records and nursing chart. These data not only provide infrastructure for daily clinical practice, but also can help to inform clinical studies. It is technically challenging to integrate and cleanse medical data from a variety of sources. Although there are several open access critical care databases from western countries, there is a lack of this kind of database for Chinese adult patients. We established a critical care database involving patients with infection. A large proportion of these patients have sepsis and/or septic shock. High-granularity data comprising laboratory findings, baseline characteristics, medications, ICD code, nursing charts and follow-up results were integrated to generate a comprehensive database. The database can be utilized for a variety of clinical studies. The dataset is fully accessible at PhysioNet (https://physionet.org/content/icu-infection-zigong-fourth/1.0/).